2020
DOI: 10.15403/jgld-2263
|View full text |Cite
|
Sign up to set email alerts
|

Screeners vs. Non-screeners for Colorectal Cancer among People over 50 Years of Age: Factual and Psychological Discriminants

Abstract: Background and Aims: Colorectal cancer (CRC) is the third most frequent form of cancer worldwide, and approximately one third of cases have a positive family history of CRC or associated cancers. Colonoscopy is one of the most effective methods of screening for CRC. Uptake of colonoscopy is suboptimal, and many countries lack a national screening programme. Our study aims at exploring and ranking several factual and psychological variables according to their accuracy in discriminating between screeners and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Jaroslaw Regula 1,2 Po p u l at i o n a d h e re n c e t o c a n c e r s c r e e n i n g re c om m e n d at i on s i s n ot satisfactory in many countries. Public Health organizations have struggled to find ways to improve the situation.…”
Section: To Be Screened or Not To Be…? Psyche First?mentioning
confidence: 99%
See 2 more Smart Citations
“…Jaroslaw Regula 1,2 Po p u l at i o n a d h e re n c e t o c a n c e r s c r e e n i n g re c om m e n d at i on s i s n ot satisfactory in many countries. Public Health organizations have struggled to find ways to improve the situation.…”
Section: To Be Screened or Not To Be…? Psyche First?mentioning
confidence: 99%
“…Research is ongoing; however, no ideal methodology has been found, so far. In this issue of the Journal of Gastrointestinal and Liver Diseases two very interesting and valuable research studies on this topic are presented [1,2].…”
Section: To Be Screened or Not To Be…? Psyche First?mentioning
confidence: 99%
See 1 more Smart Citation
“…Cronbach’α coefficients were 0.822–0.964 for the subscales, and item-total correlations ranged from 0.422 to 0.912. 24 , 25 Although the CRCSBS overlaps with CCHBMS in three core concepts, the items used to measure the construct differ. Compared with CCHBMS, CRCSBS measures the psychological structures of CRC screening more specifically (33 items), while CCHBMS has only 17 items related to screening (other items are related to disease).…”
Section: Introductionmentioning
confidence: 99%